What are the roles of teachers for drug abuse prevention? - Elisa Dwi P, Ira Nurmala, Muthmainnah, Riris Diana R, (Opción, 2019)
The purpose of this study was to determine the role of teachers on the sustainability of the peer education program as an effort to prevent drug abuse in high schools via a narrative qualitative research method. The result showed that the teachers played an active role in running peer education programs in schools until 2014 when they were given a task by the city government. In conclusion, the researcher suggested the teachers increase their commitment and also all school members to advocate the government to continue the programs related to peer education in an integrated manner